Two Impacts of Arctic Rapid Tropospheric Daily Warming From Different Warm Temperature Advection on Cold Winters Over Northern Hemisphere. Issue 9 (12th September 2019) - Wang, Cen; Ren, Baohua; Zheng, Jianqiu
Abstract: A number of previous studies show that the long‐term Arctic winter warming causes severe cold over East Asia and North America. We use the atmospheric data from National Centers for Environmental Prediction/National Center for Atmospheric Research Reanalysis to define the Arctic rapid tropospheric daily warming (RTDW) events that in one day, Arctic average 1, 000‐hPa air temperature is over 3σ warmer anomaly in situ winter. We find that main warm temperature advection of the RTDW events is from Atlantic Ocean and Pacific Ocean, named the Atlantic pattern and the Pacific pattern, respectively. The RTDW events of different warm temperature advection have different vertical distributions of warming. Therefore, different polar vortex splitting is induced and the splitting of polar vortex means movement of the cold air mass. The impacts of RTDW events on the Northern Hemisphere cold winter are mainly through the Asia‐Europe path caused by the Atlantic pattern and the North America path caused by the Pacific pattern. As for the Asia‐Europe path, the cold air invades the northern hemisphere from northwest Europe to Southeast Asia throughout the entire Eurasian continent. In the case of the North America path, the negative temperature anomalies are located in the west of Canada and America. The different warm temperature advection of RTDW events leads to different regions of the polar cold air mass invasion through different paths. Our results may help find out where the severe cold events impact on after the Arctic RTDW events with the occurrence of different warm temperature advection. Plain Language Summary: In our research, we show that there are two impacts of Arctic rapid tropospheric daily warming events on cold winters over Northern Hemisphere. The Arctic rapid tropospheric daily warming with warm temperature advection from Atlantic will cause cooling in Asia‐Europe and from Pacific will cause cold air outbreaks in North America in the next few days. Key Points: Main warm temperature advection of rapid tropospheric daily warming events is from Atlantic Ocean and Pacific Ocean Impacts of rapid tropospheric daily warming events on Northern Hemisphere cold winter are mainly manifested as two paths